Estabilidad de los parámetros cuantitativos del electroencefalograma en atletas de boxeo - Brown Martínez, M.; Nápoles, R-L.; González Acevedo, V. H.; Mendoza Quiñones, R. (Revista Cubana de medicina del deporte y la cultura fisica, 2021)
Introduction: Physiological recovery from sport-related mild traumatic brain injury may last longer than clinical abnormalities, so the possibility of quantifying neurometabolic physiological indices would be of great value for the follow-up and management of these injuries. Quantitative Electroencephalogram (EEG) methods represent an alternative to the study of these alterations. Objective: To identify differences of quantitative resting state EEG parameters between two sessions in boxing athletes. Methods: EEGs were obtained in a group of athletes with no history of traumatic brain injuries in two different time periods. The differences of the quantitative parameters of the broad band model (Absolute Power, Relative Power and Average Frequency of each frequency band) and narrow band (Energy) were analyzed. T student test with permutations for dependent samples was applied. Results: No statistically significant differences were found in narrow band analysis. In broad band model, no global significant statistical differences were found, only a significant difference was observed in the univariate analysis of Relative Power and Mean Frequency in one derivation. Conclusion: These results suggest a good stability of the quantitative EEG parameters, which indicates the value of these neurophysiological indicators in the follow- up or monitoring of brain function in athletes of these sports.